Female gaze dan negosiasi agensi perempuan dalam struktur patriarki: Analisis atas film Yuni (2021) - Aprillia, Haura Jauza; Munasiz, Ni’ma Raasyidatun Nazia; Noor, Firdaus (Jurnal Mahasiswa Komunikasi Cantrik, 2026)
This study analyzes the negotiation of female agency amid the constraints of patriarchal structures in the film Yuni (2021) through the lens of the female gaze. The method used is a descriptive qualitative one, integrating analyses by David Bordwell and Kristin Thompson, as well as Roland Barthes’s semiotics, across three levels of meaning: denotation, connotation, and myth. The results indicate that patriarchal structures operate through the normalization of early marriage, restrictions on educational opportunities, and communal mythical terror manifested in taboos, rejection of marriage proposals, and the myth of virginity. Based on the narrative causal chain, female agency is proven not to be static but rather an active agent. The process begins with symbolic negotiation to maintain autonomy—represented through an obsession with the color purple—which then accumulates into open resistance. The pinnacle of agency is manifested in the protagonist’s subversive act of consciously sabotaging the virginity myth and fleeing a forced marriage. From a female-gaze perspective, the camera rejects the male gaze and positions women as central subjects, intimately